PELVIC FLOOR KINESITHERAPY FOR PREGNANT AND POSTPARTUM WOMEN - Ogurlić, Ranka (Medicinski časopis, 2023)
The aim of this study was to examine the effect of pelvic floor kinesitherapy in the prevention and treatment of urinary incontinence in pregnant women and mothers. Through a systematic review of papers published from 2017 to 2022, the two authors selected potential papers in October 2021 to April 2022 at PubMed, Physiotherapy Evidence Database and Cochrane Library databases according to pre-established criteria, using the keywords "pelvic floor exercises" bottom ", “urinary incontinence "," pregnancy "," prevention "," prenatal period "and" postnatal period”. Works older than five years, works that were not available in full text or written in English are excluded. Using Jovell and Navarro-Rubio studio designs, the authors classified and evaluated potential works. The search resulted in 73 papers that met the set criteria, but 8 were included in the research. The results confirm that prenatal exercises of moderate intensity reduce urinary symptoms, involuntary swelling of urine and affect the improvement of pelvic floor muscle contractility and slower development of urinary incontinence. Structured supervised training increases the strength of the pelvic floor muscles and reduces the symptoms of urinary incontinence. This review of the literature confirmed the health benefits of kinesitherapy in the prevention, reduction of the frequency and intensity of urinary incontinence and the improvement of the quality of life in pregnancy and the postnatal period. Health professionals can make a significant contribution to the education of pregnant women and mothers, and the priority is to develop standardized programs in which kinesitherapy, as an integral part of the educational program, will be effectively applied.